PEMBUATAN GAME 2D ONLINE CROSS-PLAY MULTIPLAYER CO-OP PLATFORMER “SHAPE SURVIVOR” - Jonathan Sunarjo; Jeanny Pragantha; Darius Andana Haris (Fakultas Teknologi Informasi Universitas Tarumanagara, 2021)
This game was created using the Unity game engine with C# as programming language. The goal of this game is to complete stages by playing cooperatively with 2 to 4 players. At each stage players will have to dodge various enemy attack to survive and clear the stage. Testing is done by blackbox testing, alpha testing by the supervisor, and beta testing by 32 respondents through a questionnaire. The test results show that players enjoy the multiplayer aspect and have fun with the game.